Students' Perceptions of Equal Opportunities for Higher Education: Persepsi Mahasiswa Terhadap Persamaan Kesempatan Memperoleh Pendidikan Tinggi - Fithriana, Noora; Firdausi, Firman (Pedagogia : Jurnal Pendidikan, 2020)
The research aim was measuring perception of students to equality of opportunity to get higher education at Tribhuwana Tunggadewi University. To meet the aim and collect the primary data, a questionnaire survey was held to 326 Tribhuwana Tunggadewi active students in the year of 2019 by simple random sampling. Data validation was with construct validity and Alpha Cronbach. The analyzed data was with a quantitative technique by Microsoft Excel and IBM SPSS 22. The research results measured from the prospects that most students perceived “yes” the admission pathways were diverse (M = 6); the admission phases were enough (M = 6); the information and requirements were clear (M = 6); the campus promotion got to school (M = 5); most students perceived admission opportunity to all class (M = 6); and most students perceived “no” ethnic discrimination when registering (M = 4). From the means equality, most students perceived “yes” the admission test was acceptable for all registrants (M = 6); the general test informed the score to the registrants (M = 6); the registration rules equal for all registrants (M = 6); the general test informed schedule before (M = 6); the admission considered achievements, interests, and talents (M = 6); and the applicants passed the general test accepted (M = 6). The research results had a measurement score if it was true significant that the mean of perception equals to 6 of the undergraduate students perception.